Caracterização termomecânica e magnética de uma liga Ni-Mn-In com memória de forma ferromagnética - Alves, Ricardo Francisco (2018)
Ferromagnetic Memory Leagues (LMFF) that can be controlled by magnetic field have attracted considerable interest for applications such as magnetic actuators. The alloys of the Heusler NiMnGa system show a high magnetic field induced deformation, reaching values higher than 10%. However, there are some problems in the application of these LMFF, for example, high cost due to the expensive constituent element Ga, as well as a low martensitic transformation temperature (Ms) and a Curie temperature (Tc) below 100 ° C which are insufficient for actuators. In order to circumvent this limitation, new Heusler systems have been extensively studied in recent years, among which we can mention NiMnIn, NiMnSn and NiMnSb, however, they are extremely fragile, which makes it difficult to quantify the shape memory effect (EMF) and superelasticity ( SE) for these alloys by conventional mechanical testing methods (traction and compression). An alternative to overcome this difficulty would be the use of instrumented nanoindentation to obtain the mechanical properties (EMF, SE, modulus of elasticity and hardness) of these alloys. A Ni50Mn34In16 alloy was produced in a controlled atmosphere induction furnace. After the casting process the alloy is characterized microstructurally by X-ray fluorescence, X-ray diffraction, optical microscopy, scanning electron microscopy, differential scanning calorimetry (DSC) and magnetometry of vibrating sample and mechanically through the ultramicrodureza test with the penetrator Berkovich. It was observed that the alloy showed a deviation of composition with respect to the nominal percentages. Through the X-ray diffractograms of the crude and heat treated samples, it was observed the presence of the phases L21 and Mn3Ni2In. It was observed through the DSC results that the degree of chemical homogeneity affects the phase transition temperatures. From the magnetic hysteresis curves it was found that the gross sample of fusion presents a ferromagnetic behavior, whereas the thermally treated showed tendency to paramagnetism (with remnants of ferromagnetism). Through the ultramicrodureza tests, it was observed that the heat treatment caused a decrease in modulus of elasticity and hardness. In addition, the treated alloy presented a superelastic recovery greater than the crude melt.